HAK-HAK PEREMPUAN DALAM SURAT AL-AHZAB AYAT 33: SEBUAH PENDEKATAN HERMENEUTIK - Naili Fauziah Lutfiani (Islamic University of Indonesia, 2017)
This paper was intended to describe that it is highly recommended and important to have a sophisticated understanding of the qur’an al-Ahzab verse 33 concerning the rights of women to take action outside of domestic work such as career, social, and education. Because of the misunderstanding and misinterpretation of the Qur’anic text of al-Ahzab verse 33, there are still people with narrow paradigms that cause the enslavement of women in domestic household affairs only which is very contradictory to the moral message of the Qur’an. Therefore, this paper will present the moral message that is explicitly contained in the Qur’an al-Ahzab verse 33. The study deploys a descriptive- analytic method using hermeneutic methodology, and the data are gathered through library reviews. The study finds that in Qur’an al-Ahzab verse 33, women do not only have domestic duties as housewives, but also have rights to take part in the world of work or career, social world, and education. It has to be surely maintained to develop the potential of women as fellow servants of God who both have the potential and also at the same time play a role to help aspects of the family economy. What happened in some societies is an output from the interpretation of the normative or textual text of the Qur’an that makes a gap between men and women which excludes the message of ethics of the Qur’an that put forward the value of equality in a proportional context. Keywords: Womens right, hermeneutics, equality